A Targeting Nanotherapy for Abdominal Aortic Aneurysms - Cheng, Juan; Zhang, Runjun; Li, Chenwen; Tao, Hui; Dou, Yin; Wang, Yuquan; Hu, Houyuan; Zhang, Jianxiang (Journal of the American College of Cardiology, 2018)
Abdominal aortic aneurysm (AAA) is a leading cause of mortality and morbidity in the elderly. Currently, there remain no effective drugs that can prevent the growth of aneurysms and delay aneurysm rupture in the clinical setting. The aim of this study was to develop a nanotherapy that can target aneurysms and release drug molecules in response to the inflammatory microenvironment. Using a reactive oxygen species (ROS)-responsive nanoparticle and a candidate drug rapamycin, in combination with a peptide ligand for integrin and biomimetic cloaking with macrophage cell membrane, a nanotherapy was developed. Its effectiveness was demonstrated by in vitro and in vivo studies. Based on a facile and translational method, a rapamycin-loaded responsive nanotherapy was successfully prepared, which could release drug molecules upon triggering by the high level of ROS. In cells associated with the development of AAAs, the nanotherapy significantly inhibited calcification and attenuated ROS-mediated oxidative stress and apoptosis. By passively targeting aneurysms and releasing drug molecules in response to the inflammatory microenvironment, the intravenously injected ROS-responsive nanotherapy more effectively prevented aneurysm expansion in AAA rats than a nonresponsive control nanotherapy. After decoration with a peptide ligand cRGDfK and macrophage cell membrane, the aneurysmal targeting capability and therapeutic effects of a ROS-responsive nanotherapy with a mean diameter of 190 nm were further enhanced. Moreover, the nanotherapy showed a good safety profile in a preliminary safety test. The multifunctional nanotherapy can be further studied as a promising targeted drug for treatment of aneurysms. The underlying design principles enable the development of a broad range of nanomedicines for targeted therapy of other vascular diseases. [Display omitted]